2015
DOI: 10.1016/j.envres.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measures of perfluoroalkyl substances (PFAS) in serum of Gullah African Americans in South Carolina: 2003–2013

Abstract: Background Charleston Harbor has elevated concentrations of PFAS in dolphins, but local human exposure data are limited. Objectives We sought to describe PFAS serum concentrations’ temporal trends among Gullah African American residents of coastal South Carolina. Methods Longitudinal measures of PFAS in blood serum from a Gullah clinical sample, without lupus, were examined using spaghetti plots and visit-to-visit change scores (e.g., differences in concentrations between visits) among the 68 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Our observed decreases in PFOS and PFOA were similar to other studies of similar timeframe ( Worley et al, 2017 ). Focusing on PFOS, another study of Gullah African Americans from coastal South Carolina showed that PFOS dropped approximately nine percent each year between 2003 and 2013 ( Gribble et al, 2015 ) which is consistent with our observations in residents of Anniston, Alabama. Finally, it is hard to interpret and compare our observations of possibly increased circulating levels of HFPO-DA over time because few studies in the United States focusing on matched serum samples have reported on HFPO-DA levels using analytical methodologies with comparable LODs.…”
Section: Discussionsupporting
confidence: 89%
“…Our observed decreases in PFOS and PFOA were similar to other studies of similar timeframe ( Worley et al, 2017 ). Focusing on PFOS, another study of Gullah African Americans from coastal South Carolina showed that PFOS dropped approximately nine percent each year between 2003 and 2013 ( Gribble et al, 2015 ) which is consistent with our observations in residents of Anniston, Alabama. Finally, it is hard to interpret and compare our observations of possibly increased circulating levels of HFPO-DA over time because few studies in the United States focusing on matched serum samples have reported on HFPO-DA levels using analytical methodologies with comparable LODs.…”
Section: Discussionsupporting
confidence: 89%
“…Individuals may also differ in their capacity for bodily storage and excretion of PFOA. For example, there is some evidence of small effects of age and sex on PFOA retention ( Brede et al 2010 ; Zhang et al 2013 ; Gribble et al 2015 ), potentially affecting individual-specific values for the half-life and steady-state ratio. At present these effects are not very well characterized, but their potential impacts can be explored by modifying those parameters in the “Advanced options” section.…”
Section: Discussionmentioning
confidence: 99%
“…Interindividual variability in consumption rates and toxicokinetics can affect the contribution of drinking water to serum PFAS concentrations. Uptake and elimination of PFAS varies depending on age, race, menstrual status, childbirth, and breastfeeding (Gribble et al. 2015; Wong et al.…”
Section: Introductionmentioning
confidence: 99%